Volkanostratigrafi Inderaan Jauh Kompleks Gunungapi Gede dan Sekitarnya, Jawa Barat, Indonesia - Agustin, Fitriani; Bronto, Sutikno (Jurnal Geologi dan Sumberdaya Mineral, 2019)
Remote sensing technology greatly helps to identify the various of volcano features, including active, old and ancient volcanoes. The aim of this  paper is intended to introduce various volcanic features in the Gede Volcano Complexs (GVC) and souronding area; compose volcanostratigraphy; and estimate the history of the volcanoes. The method used is a visual interpretation 9 meters spatial resolution of Digital Elevation Model (DEM) TerraSar-x image. Indonesian Stratigraphy Nomenclature Guide 1996 was implemented in vocanostratigraphy unit classification, involving Arc, Super Brigate, Brigate, Crown and Hummockly. Based on the interpretation the DEM image, volcanostratigraphic unit the Gede Volcano Complex consists of Bregade Masigit (Br. M.), which consists of Joklok (Gm.J.) and Gegerbentang (Gm.G.) Hummocs; Crown Lingkung (Kh.L.) consisting of Pangrango (Gm.P.), Situ Gunung (Gm Sg.), Cikahuripan (Gm.Ck.), Pasir Prahu (Gm.Ph) Hummocs; Gege Crown (Kh.G.), which is located in the east of Lingkung Crown. The Gede Crown consists of Gumuruh humock (Gm.Gh.), Gunung Gede lava flows (LG 1,2,3,4,5), and giant debrise avalances (gv-G). The geological mapping based volcanostratigraphy is very useful for exploration of mineral and energy resources, as well as geological hazards.Keywords : volcanostratigraphy, DEM TerraSar-x image, Gunung Gede Complexs.DOI: 10.33332/jgsm.2019.v20.1.9-16